Городища півдня Житомирщини - Вітрик, І.С. (Археологія, 1995)
В інформації подаються дані про результати розвідок на шести городищах, археологічні відомості про які були неповними, вимагали уточнення чи були відсутні. В ходе археологических разведок 1988—1989 гг. экспедицией ИА НАН Украины были исследованы шесть городищ. В археологической литературе содержались лишь сведения о существовании подобных памятников у сел Гульск, Малые Кошарища, Щиглиевка, более известно было городище у пгт Мирополь, два городища (сс. Приветов, Гульск) обследовались впервые. В результате работ были составлены их планы и собраны материалы для датировки. During archaeological surveys carried out by the Institute of Archaeology of the Academy of Sciences of Ukraine in 1988—1989 six settlements of the south of the Zhitomir Region were examined. The archaeological literature has in its disposal only information on existence of settlements near villages Gulsk, Malye Kosharishcha, Shchiglievka; a settlement near town of Miropol is known somewhat better; two settlements near villages Privetov and Gulsk are examined for the first time. As a result of the studies carried maps of all these settlement have been compiled and information for their dating is obtained.